PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN METODE DEMONSTRASI TERHADAP PENGETAHUAN, SIKAP DAN KETERAMPILAN CUCI TANGAN PAKAI SABUN (CTPS) SEBAGAI UPAYA PENCEGAHAN DIARE SISWA SDN 022BALIKPAPAN - Dhea Ayu Yusrifa; Yona Palin, Emelia Tonapa (Jurnal Kesehatan, 2025)
Backgorund : According to the World Health Organization (WHO), 100 thousand children die from diarrhea, 25.5% of deaths in children aged 4-11 years are caused by diarrhea. 40 to 60% of children's diarrhea is caused by rota virus contamination by not washing their hands. WHO states that washing hands with soap can reduce diarrhea rates by up to 47% (WHO, 2018). Efforts to prevent diarrhea can be done by implementing the habit of washing hands with soap (CTPS) for elementary school age children. Objective : The main aim of this research is to determine the effect of health education using the demonstration method on CTPS knowledge, attitudes and skills among students at SDN 022 Balikpapan. Methods : This research uses a one group pretest-posttest design. The location of this research was SDN 022 Balikpapan. The respondents in this research were 29 students. Result : The results of this study show that there are differences in knowledge, attitudes and skills after being given the intervention with the Wilcoxon test p-value 0.000 (<0.05). Conclusion : So it can be concluded that there is a significant influence on the knowledge, attitudes and skills of respondents between before and after being given research intervention using the demonstration method.